The impact of AC-Free Trade Area on the performance of industrial sectors in Indonesia - Eko Wahyudi; Budiono Budiono (Universitas Hayam Wuruk Perbanas, 2014)
ASEAN-China free trade has an impact on economic performance among sectors in Indonesia. One of the sectors affected by the free trade is the industrial sector that is the largest contributor to national income sector in Indonesia. This study is intended to explain the impact of the ASEAN-China free trade on the performance of the industrial sector in Indonesia. This is a descriptive qualitative research aimed to qualitatively analyze and describe the impact of the ASEAN-China free trade on the industrial sector in Indonesia. It can be concluded that the performance of the industrial sector has decreased during the implementation of the ASEAN- China free trade.Â This is indicated by (1) the contribution of industrial sector to GDP which decreases and the contribution to employment has no significant change, (2) the industrial sector grew on average per year lower than the average growth of GDP, (3) the contribution of the industrial sector in Indonesia's total exports tend to decrease too. Industrial exports grew on average per year lower than the growth of total exports, (4) the contribution to total imports of industrial products Indonesian non-oil imports increases. Imports of industrial products experienced average growth per year which is higher than the growth in total non-oil imports, (5) the percentage of realization of investment (both domestic and FDI) in the industrial sector to total investment in Indonesia also tends to decrease, (6)Â the percentage of bank extended creditÂ to the industrial sector tends to decrease .